MPGN Type 3 Associated with Pemphigus Herpetiformis Mimicking PGNMID and Dermatitis Herpetiformis - Shimizu, Yoshio (Case Rep Nephrol Dial, 2019)
A 45-year-old man suffering from dermal blistering disease with proteinuria and hematuria underwent renal biopsy. The renal biopsy specimen suggested proliferative glomerulonephritis with monoclonal IgG deposits under routine light, immunofluorescence and electron microscopy. The staining for IgG subclasses (IgG1 and IgG2) and κ/λ light chain indicated secondary immune complex type MPGN type 3. The patient had been diagnosed as having dermatitis herpetiformis (DH), a phenotype of gluten hypersensitivity prior to the appearance of the renal abnormality. Although common autoantibodies might be related to the pathogenesis of disorders in the skin and kidney, DH is mainly driven by IgA autoantibody, while MPGN is induced by IgG immune complexes. IgA was not observed in the glomeruli by immunofluorescence. Neither the examination for DH specific autoantibodies nor HLA-DQB1 genotype supported the diagnosis of DH. Reassessment of the skin biopsy record revealed that the blister was localized in the epidermis, suggesting pemphigus herpetiformis by IgG class anti-epidermal autoantibody, which also affected the renal disorder.